2021
DOI: 10.1007/s00234-021-02737-4
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion imaging with arterial spin labeling (ASL)–MRI predicts malignant progression in low‑grade (WHO grade II) gliomas

Abstract: Purpose Predicting malignant progression of grade II gliomas would allow for earlier initiation of treatment. The hypothesis for this single-centre, case–control study was that the perfusion signal on ASL-MRI predicts such malignant progression in the following 12 months. Methods Consecutive patients with the following criteria were included: ≥ 18 years, grade II glioma (biopsied or resected) and an ASL-MRI 6–12 months prior to malignant progression (cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…Finally, ASL can be used for prognosis prediction of patients with glioblastoma, as low‐perfused gliomas appear to be associated with longer event‐free and OS 64 . Moreover, malignant progression in patients with grade 2 glioma can be predicted using ASL 67 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, ASL can be used for prognosis prediction of patients with glioblastoma, as low‐perfused gliomas appear to be associated with longer event‐free and OS 64 . Moreover, malignant progression in patients with grade 2 glioma can be predicted using ASL 67 …”
Section: Resultsmentioning
confidence: 99%
“…64 Moreover, malignant progression in patients with grade 2 glioma can be predicted using ASL. 67 VALIDATION. The 2015 ISMRM Perfusion Study Group ASL recommendations resulted from a major effort to standardize ASL for clinical applications in the brain.…”
Section: Aslmentioning
confidence: 99%
“…Future studies should focus on developing ML/DL models by combining different data sources (i.e., clinical, radiomic, semantic and PWI/DWI), which are correlated and may provide complementary information [ 95 ] for improving the clinical decision-making tasks [ 96 ]. Moreover, given the proven importance of quantitative techniques such as PWI and DWI, future ML/DL models should leverage the wealth of data provided by novel and more refined diffusion and perfusion techniques [ 97 , 98 , 99 , 100 , 101 ], potentially also including information upon cerebral metabolism [ 99 , 102 ]. By integrating all these data into a single multimodal model, further improvements in performance could be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Besides categorization into LGG and HGG, ASL-derived tumor perfusion has been associated with multiple markers that can impact treatment decision making and survival, including isocitrate dehydrogenase status, methylguanine-DNA methyltransferase promoter methylation, p53 status, as well as vascular endothelial growth factor expression and tumor microvascular density [94][95][96][97]. Furthermore, it has also been suggested that malignant progression within 12 months could be predicted with ASL-based perfusion imaging in patients with LGG, with a sensitivity of 73 %, specificity of 82 %, and odds ratio of 12 [98].…”
Section: Gliomasmentioning
confidence: 99%